Futureproofing : navigating and thriving in uncertain futures - Chun, Win Ee (2019)
We live in a world increasingly characterised by uncertainty, volatility and complexity. To cope in such environments, governments and companies have started to engage in futureproofing – anticipating plausible challenges and obstacles in advance and preparing for them to not just survive, but thrive. While mainstream media has highlighted the need and benefits for futureproofing, it has yet to be studied academically as an individual difference. In this thesis, we aimed to establish futureproofing as a cognitive-motivational trait that we anticipate to be adaptive going forward. We developed a scale to measure futureproofing, establishing its psychometric properties. The futureproofing scale comprised of two factors as predicted, and demonstrated good reliability, convergent validity and divergent validity, as well as concurrent validity. We also demonstrated that it has incremental validity in predicting domain-specific futureproofing behaviours beyond existing future-oriented thinking or proactive coping constructs, establishing its unique utility. Additionally, we speculated that futureproofing is a malleable trait that can be modulated drawing from research on interventions to increase future-oriented thinking. Thus, futureproofing is potential area of intervention or personal development to improve a multitude of outcomes in life. Implications and further research avenues were discussed.